Echo chambers can emerge without algorithmic personalization or a preference for homogeneity - Petter Törnberg (PLoS ONE, 2026)
Online ideological segregation—often described as “echo chambers”—is commonly attributed to algorithmic personalization (“filter bubbles”) or users’ preferences for like-minded environments. We propose a different mechanism. Using a minimal agent-based model, we show that strong segregation can arise even without algorithmic personalization and without users preferring homogeneous environments. Even when users exit communities only after finding themselves almost entirely surrounded by disagreement, cascading exits can push initially mixed communities toward high homogeneity. Once small imbalances arise, feedback between exit and regrouping generates a self-reinforcing process of system-level sorting. Extending the model further reveals that algorithmic personalization can, under some conditions, reduce segregation by lowering dissatisfaction, slowing exit cascades, and stabilizing mixed communities. As an empirical illustration, a longitudinal analysis of the subreddit r/MensRights shows that users whose language is more distant from the community’s evolving semantic center are more likely to exit. Taken together, these findings suggest that echo chambers need not depend on users seeking homogeneous environments or algorithmic personalization alone, but can also emerge from exit dynamics in the interaction structures characteristic of online platforms. More broadly, they show how interventions aimed at individual exposure can produce aggregate dynamics that differ from their intended effects, complicating both scientific and policy debates over online polarization.